Condição humana, condição cidadã: um ensaio sobre a dignidade da política e os desafios do novo Estado democrático - Adelia Maria Miglievich Ribeiro (Ciências Sociais Unisinos)
Starting from Hanna Arendts concept of action as freedom that makes possible the construction of the public space, the article discusses the dignity of politics expressed in the exercise of power as an inherent element of the human condition. In this sense, it distinguishes power from coercion and relates it to the idea of participation in community life, of which nobody should be deprived if they are to be able to fulfill themselves as human beings. The degradation of politics is expressed in the suppression of action and thus of power. In the view of Boaventura de Souza Santos, this jeopardizes the modern social contract, demanding its renewal through the public powers commitment to the consolidation of processes of social inclusion. The author argues that such a redefinition of the public agenda implies the recognition of the other as a human being and that this perception, according to Charles Taylor, is not as obvious as it seems because of the socially made moral classifications. To promote citizenship is to provide the totality of individuals with the human condition. This assumption suggests a perception of the dignity of human life in any circumstances. The recognition of the generic other in their relevance is, however, inseparable from the strengthening of public power in terms of coordinating the market and distributive democracy. Key words: social theory, postmodern critique, social movements.